Predictors of early and late mortality after the treatment for early gastric cancers. Issue 4 (4th November 2021) - Ogata, Yohei; Hatta, Waku; Ohara, Yuki; Koike, Tomoyuki; Abe, Hiroko; Saito, Masahiro; Jin, Xiaoyi; Kanno, Takeshi; Uno, Kaname; Asano, Naoki; Imatani, Akira; Yamamura, Akihiro; et al.
Abstract : Objectives: Although many patients with early gastric cancers (EGCs) die of non‐gastric cancer‐related causes, the association of the risk categories of lymph node metastasis (LNM) with all‐cause mortality remains unclear. We aimed to clarify the predictors of early and late mortality, separately. Methods: Patients with endoscopic resection or gastrectomy for EGCs between 2003 and 2017 were retrospectively enrolled. We analyzed predictors for early and late mortality, including risk categories of LNM, treatment method, and nine non‐cancer‐related indices, separately, with a cut‐off value of 3 years. Results: We enrolled 1439 patients with a median follow‐up period of 79 months. The 5‐year overall survival rate was 86.8%. In the multivariate Cox analysis, the most important predictors for early and late mortality were age ≥85 years (hazard ratio [HR] 2.88 and 4.54, respectively) and Eastern Cooperative Oncology Group Performance Status ≥2 (HR 3.00 and 4.19, respectively). Charlson comorbidity index ≥2 (HR 2.76 and 1.99, respectively), American Society of Anesthesiologists Physical Status ≥3 (HR 2.35 and 1.79, respectively), and C‐reactive protein/albumin ratio ≥0.028 (HR 2.30 and 1.58, respectively) were also predictors for both early and late mortality. Male (HR 2.26), intermediate‐ (HR 2.12)/high‐risk (HR 1.85) of LNM in eCura system, and sarcopenia evaluated by the psoas muscle mass index (HR 1.70) were predictors for early mortality. Conclusion: The combined assessment of multiple predictors might help to predict early and/or late mortality in patients with EGCs. The eCura system was associated with early mortality.